(untitled) (Research, Society and Development, 2024)
Objective: To map, through scientific literature, the good practices used for concurrent and terminal disinfection of beds in Intensive Care Units. Method: Scope Review Protocol developed in accordance with the guidelines of the Joanna Briggs Institute manual and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA – ScR) checklist. The search sources will be: Medical Literature Analysis and Retrievel System Online (MEDLINE) via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Latin American and Caribbean Literature in Health Sciences (LILAC), SCOPUS, Web of Science, EMBASE. And as a source of gray literature, the Digital Library of Theses and Dissertations (BDTD) will be used. Studies that meet the inclusion criteria will be considered, without restrictions on language and time frame. Publications will be selected by two reviewers, independently, and if necessary, a third reviewer will participate in cases of disagreement. Data will be extracted using the instrument developed by the reviewers, and the research results will be presented through charts, graphic flowcharts and tables and analyzed descriptively. It is expected that with the development of this scope review, existing good practices for disinfecting beds in Intensive Care Units can be mapped, and that it may also be possible to disseminate knowledge that directly impacts the quality of care provided in health services promoting a culture of safety.